Alcohol Modulation of Cardiac Matrix Metalloproteinases (MMPs) and Tissue Inhibitors of MMPs Favors Collagen Accumulation. (19th August 2013) - El Hajj, Elia C.; El Hajj, Milad C.; Voloshenyuk, Tetyana G.; Mouton, Alan J.; Khoutorova, Elena; Molina, Patricia E.; Gilpin, Nicholas W.; Gardner, Jason D.
<x xml:space="preserve">Abstract</x> Background Chronic alcohol consumption has been shown in human and animal studies to result in collagen accumulation, myocardial fibrosis, and heart failure. Cardiac fibroblasts produce collagen and regulate extracellular matrix (ECM) homeostasis through the synthesis and activity of matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs), with the balance of MMPs/TIMPs determining the rate of collagen turnover. Dynamic changes of MMP and TIMP expression were reported in alcohol‐induced hepatic fibrosis; however, the effect of alcohol on MMP/TIMP balance in the heart and cardiac fibroblasts is unknown. We hypothesized that alcohol exposure alters cardiac fibroblast MMP and TIMP expression to promote collagen accumulation in the heart. Methods Cardiac fibroblasts isolated from adult rats were cultured in the presence of alcohol (12.5 to 200 mM) for 48 hours. MMP, TIMP, and collagen type I and III expression were assayed by Western blot analysis. Hydroxyproline (HPro) was used as a marker of collagen production. The in vivo cardiac effects of ethanol (EtOH) were determined using rats exposed to EtOH vapor for 2 weeks, resulting in blood alcohol levels of 150 to 200 mg/dl. Cardiac collagen volume fraction (CVF), as well as MMP, TIMP, and collagen expression, was assessed. Results EtOH‐exposed rats exhibited up‐regulation of TIMP‐1, TIMP‐3 and TIMP‐4 in the heart, with no significant increases in MMPs. Cardiac fibroblasts exhibited transformation to a profibrotic phenotype following exposure to alcohol. These changes were reflected by increased α‐smooth muscle actin and collagen I and III expression, as well as increased collagen secretion. In vivo EtOH exposure also produced fibrosis, indicated by increased CVF and expression of collagens. Conclusions Alcohol exposure modulates cardiac fibroblast MMP/TIMP expression favoring a profile associated with collagen accumulation. Our data suggest that this disrupted MMP/TIMP profile may contribute to the development of myocardial fibrosis and cardiac dysfunction resulting from chronic alcohol abuse.